Foraminifera Community Structure in Gili Kapal, Sambalia District, East Lombok as A Learning Resource for Invertebrate Zoology - Ariadi, Muhammad Rojiman; Santoso, Didik; Ilhamdi, Mohammad Liwa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Gili Kapal is a small island filled with sand. The sand on Gili Kapal is caused by coral fragments and shells of benthic Foraminifera which dominate. Foraminifera is a group of single-celled animals that belong to the Protozoa Phylum of the Class Sarcodina and can be used as bioindicators to determine various environmental changes in the ocean. This study aims to determine Foraminifera species and community structure in the form of species diversity index, species evenness index and dominance index of Foraminifera species in Gili Kapal, Sambalia, East Lombok. Sampling was carried out using a corer sampler made of PVC pipes with the Purposive Sampling method in January 2022. The species diversity index, species evenness index, and species dominance index were analyzed as part of the data for this study. According to the study's findings, there are five species across four genera and three families. Sequentially the Foraminifera species found were; Amphistegina radiata, Calcarina spengleri, Schlumbergerella neotetraedra, Schlumbergerella floresiana, and Sorites orbiculus. The species diversity index was 0.9 (low category), the species evenness index was 0.4 (low category), and the species dominance index was 0.6 (medium category). It can be concluded that, sequentially the constituents of the Foraminifera community on Gili Kapal are Amphistegina radiata, Calcarina spengleri, Schlumbergerella neotetraedra, Schlumbergerella floresiana, and Sorites orbiculus.